ETIKA LINGKUNGAN SISWA SEKOLAH DASAR DI PEKANBARU - Nur Salwa; Eddy Noviana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2019)
Humans have an important role in protecting nature or the environment, to preserve the environment the need for environmental ethics. The Adiwiyata program can instill environmental ethics in school residents, especially students. Research conducted to describe environmental ethics on the behavior of elementary school students around the canteen. Environmental Ethics Indicators visible around the canteen are: 1) Responsibility for the Environment, 2) Solidarity with the Environment, 3) Compassion and care for nature or the environment, 4) Do not damage the nature or the environment, 5) Live simply and aligned with nature. This type of research is descriptive research, the research instrument is observation and interviews. The results is environmental ethics did not yet exist on student behavior. This type of research is descriptive research, the research instrument is observation and interviews. The results showed that environmental ethics did not yet exist on student behavior. Student awareness in protecting the environment is still low, seen from the lack of environmental ethics in student behavior. The school should pay more attention to environmental ethics on student behavior, and make activities that can instill or enhance environmental ethics on student behavior